THE NEW URBAN AGENDA, THE INTERNATIONAL CIRCULATION OF URBAN POLICIES AND CHALLENGES OF A HUMANE URBANISM IN THE GLOBAL SOUTH - Mahesti Okitasari (Journal of Architecture&ENVIRONMENT, 2016)
In many ways international circulation of urban policies is indispensable to the spread of planning regimes. Contemporary cities in the Global South are sensitive to global, local, relational and territorial geographies, flows and fixity and the increasingly diverse stakeholders. The gradual integration of major international references associated with sustainable urbanism into local interventions combining social, economic and environmental prevention exemplifies the pervasiveness of global approaches. On the other hand, the production of cities is seasoned by the complex state-society relations as the planning practice struggles to respond to the hegemonic urban planning that are time, scale and geographically specific.  Building on this background, this paper revisits the notion of the New Urban Agenda within the international circulation of urban policies, practices and models from the standpoint of cities in the Global South. It examines the push and pull in the global process for the inclusion of initiatives that respond to the needs of Southern cities. This paper sets to explore the New Urban Agenda within the current borrowing, adaptation and hybridization of planning practices and how it can contribute to the debate of localizing the Agenda towards humane urban policies fitting to the needs of the people. This paper identifies impediments to the attainment of the New Urban Agenda as it is circulated, sets to be adapted and taken up, and mutates. This paper contributes to two conversations within planning academics on the implication of the New Urban Agenda: to the international circulation of urban policies and the making of contemporary cities in the Global South and to the struggle facing cities towards a humane urbanism.